1984
DOI: 10.1136/gut.25.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Corrosive acid ingestion in man - a clinical and endoscopic study.

Abstract: SUMMARY Sixteen patients with corrosive acid ingestion were studied. The majority of patients (n= 10) had ingested sulphuric acid, and three other patients had ingested hydrochloric acid. The extent and severity of upper gastrointestinal tract injury was determined by fibreoptic endoscopy and necropsy. All the patients had oesophageal and gastric involvement but the duodenum was spared in the majority. The injury was not considered as mild (grade I) in any of these patients; five patients having moderate (grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
1
7

Year Published

1985
1985
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 14 publications
(1 reference statement)
0
23
1
7
Order By: Relevance
“…Surgery was usually performed 7–10 days after the UGI examination. Varying degrees of residual mucosal inflammation of the gastric remnant were noted for 80% of our patients during surgery; however, edema or contraction of the stomach did not preclude gastric resection [19, 20, 21]. From analysis of the study data, it was demonstrated that antral strictures were more common than the gastric body variant.…”
Section: Discussionmentioning
confidence: 91%
“…Surgery was usually performed 7–10 days after the UGI examination. Varying degrees of residual mucosal inflammation of the gastric remnant were noted for 80% of our patients during surgery; however, edema or contraction of the stomach did not preclude gastric resection [19, 20, 21]. From analysis of the study data, it was demonstrated that antral strictures were more common than the gastric body variant.…”
Section: Discussionmentioning
confidence: 91%
“…Exposures to both acids and alkalis through ingestions can result in a wide variety of presentations, severity, and complications [4].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the situation in Western countries where alkali-induced strictures are more common, acid has been found to be a more frequent cause of strictures in India. Acid ingestion has been found to be a cause in less than 5% of the stricture cases in United States, while in India it has been found to be involved in about 70%-80% [4,[13][14][15][16]. Most of the ingestions in India are accidental rather than suicidal [15].…”
mentioning
confidence: 97%